2015
DOI: 10.1002/mds.26350
|View full text |Cite
|
Sign up to set email alerts
|

Probable RBD and association with neurodegenerative disease markers: A population‐based study

Abstract: Our findings may provide a basis for future studies intending to identify cohorts at risk for Lewy body diseases through screening of the general elderly population for RBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 34 publications
5
52
0
2
Order By: Relevance
“…Our central finding is that the prevalence of PSG-confirmed RBD is 1.06% in those aged 40-80. This estimate is higher than previous studies which screened for sleep injury [25], considerably lower than questionnaire-based studies without PSG confirmation [26,27], and notably consistent with a smaller PSG-based study [28]. On analysis of risk factors, people with RBD use more antidepressants and antipsychotics and are more likely to have smoked.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our central finding is that the prevalence of PSG-confirmed RBD is 1.06% in those aged 40-80. This estimate is higher than previous studies which screened for sleep injury [25], considerably lower than questionnaire-based studies without PSG confirmation [26,27], and notably consistent with a smaller PSG-based study [28]. On analysis of risk factors, people with RBD use more antidepressants and antipsychotics and are more likely to have smoked.…”
Section: Discussionsupporting
confidence: 64%
“…Boot et al assessed 651 patients aged over 70 years with the Mayo Sleep Questionnaire and found possible RBD in 6.7% [26]. Mahlknecht et al assessed 456 participants aged over 60 years form the Bruneck cohort with the RBD Screening Questionnaire and the Innsbruck RBD-Inventory, and found a prevalence of RBD of 4.6% and 7.7%, respectively [27]. Wong et al found that 5.9% of men and 4.1% of women in a large Chinese general population aged over 24 years screened positive on the RBD single question screen [31].…”
Section: Prevalence Estimatesmentioning
confidence: 99%
“…Patients with iRBD frequently reported NMS commonly found in advanced Parkinson's disease such as dribbling saliva, cognitive deficits, and hyposmia [42]. Moreover, the presence of RBD in the prodromal Parkinson's disease phase was associated with more cognitive deficits and with greater annual rate of cognitive decline, suggesting that RBD may be a risk factor for the development of dementia in Parkinson's disease [33 & ].…”
Section: Conversion To Synucleinopathymentioning
confidence: 99%
“…RBD [14,15] 1% The prevalence of RBD is about 0.5-1% in the general population and 2-8% in the older adult population More common (25-50%) in synucleinopathies (e.g. M. Parkinson) Sleep-related (nocturnal) eating disorders [16] …”
Section: Key Pointsmentioning
confidence: 99%
“…Neurodegeneration probable RBD is associated with neurodegenerative disease markers such as hyposmia and nonmotor symptoms [15] and over 50% of patients with idiopathic RBD develop within 5-10 years a neurodegenerative parkinsonian disorder (typically a synucleinopathy) [ [108]), RBD (limbic encephalitis, brainstem stroke, demyelinating disorders [109,110]), and RLS (e.g. spinal cord demyelination, subcortical stroke).…”
Section: Etiologymentioning
confidence: 99%